Investigation of hydration and formation of structural-mechanical properties of vegetable paste with iodine-containing raw material - Palamarek, Karina (Technology audit and production reserves, 2017)
The object of research is the technology of vegetable pastes with iodine-containing raw materials. One of the most problematic places of the research object is the cost of iodine-containing raw materials, namely, hydrobiont powders. Comparison of the price of powders made from hydrobionts with the price of traditional raw materials shows that they are not competitive enough, because they exceed the traditional one. In the course of the research, the physicochemical parameters of the pastes are used, which depend on the raw materials, added additives and process parameters, as well as rheological properties, which are characterized by effective limiting shear stress and adhesion. As a research result, the use of laminaria powder with the hydromodule from 1:4 to 1:5 and hydrobiont powder with the hydromodule from 1:5 to 1:6 is justified, which leads to an increase in the technological properties of vegetable pastes by 1.7...2.8 % and 2.7...3.9 % respectively. It is revealed that the structural and mechanical parameters of vegetable pastes increase with a concentration of hydrated laminaria powder 3 g and hydrated hydrobiont powder 48 g by 2.8 %, and the organoleptic index rises to the highest value of 4.78 points. This indicates an increase in the stickiness of the paste, improving the stability of the paste during the formation and transport. Due to this, it is determined the expediency of joint use of vegetable and protein ingredients, as well as inactivated yeast in vegetable pastes that will ensure high biological value of the product and a high level of iodine assimilation. The conducted researches allows to develop the formulation composition and technological process of obtaining rolls with vegetable paste made from iodine-containing raw materials, which is fixed in the approved technical conditions: TU U 10.8-05476322-002:2013 «Culinary products. Rolls with vegetable fillings» and technological instruction with TU U 15.8-32214657-003:2010 «Culinary products. Rolls with vegetable fillings». Thus, a broad interpretation of the problem of iodine deficiency and the research results can be used not only by specialists in the field of nutrition and the food industry, but also by endocrinologists and physicians of other specialties. This allows to recommend the developed culinary products for use for the prevention of iodine deficiency disorders.